Health nutrition and economic growth nexus: Evidence from panel Granger causality test - Benlakhdar, Abdelghani; Ikhlef, Larbi; Mammeri, Abdelouahab; Ben Amor, Tawfik (The International tax journal, 2025)
The study investigates the causal relationship between healthcare expenditure, nutrition and economic growth in 10 countries representative of the Middle East & North Africa over the period 2000:2024. Bootstrap panel Granger causality test approach is used taking into account the cross-sectional dependency and the heterogeneity in these countries. The empirical results support a bi-directional causality between economic growth and nutrition in Tunisia and Iran. The same a bi-directional causality is supported in empirical results of economic growth and health care expenditure in Algeria and way granger causality is supported in economic growth and health care expenditure in Tunisia, Saudi Arabia and Jordan. We concluded a way granger causality is supported in health care expenditure and economic growth in Morocco and Iran. We also found way granger causality in the economic growth and nutrition in Egypt, Morocco, Jordan and Lebanon. The result of the causality tests reveal a way granger causality in nutrition and economic growth in Oman.